Nepali Translation and Validation of Dental Satisfaction Questionnaire - Rai, Arbind; Shrestha, Sneha; Ayer, Ashok; Agrawal, Navin; Vikram, Mannu (Birat Journal of Health Sciences, 2022)
Introduction: Patient satisfaction is regarded as an important outcome of health care that contributes to better patient compliance and consequently offers improved clinical outcomes Dental school clinics must regulate both the clinical and academic classes in balance without hampering the needs of both the patient and students. Objectives: To develop a reliable and valid Nepali version of Dental Satisfaction Questionnaire (DSQ-N). Methodology: The English version of the dental satisfaction questionnaire (DSQ) was translated into Nepali following a standard translation process. Content validity followed by pre-testing were evaluated to obtain the final version of DSQ-N. Two hundred patients attending the Department of Conservative Dentistry and Endodontics completed the DSQ-N in the waiting room, at their convenience. Internal consistency of the questionnaire was determined by Cronbach's alpha and Principal component analysis was used to determine the construct of the scale. Result: Content Validity Index of the scale was 0.9 (S-CVI/ Avg) and alpha (Cronbach's) coefficient for the overall construct of DSQ was ≈0.83. Principal Component Analysis confirmed the internal structure of the scale and four components emerged from it. Conclusion: The translated nepali version of DSQ is a reliable and valid tool to determine patients’ satisfaction of dental care services based on the excellent content validation result together with robust internal reliability.